Handbook of social capital the troika of sociology, political science, and economics - Svendsen, Gert Tinggaard 1963-.; Svendsen, Gunnar Lind Haase 1965-. (Cheltenham, [England] Edward Elgar, 2009)
A guide to the study of bonding and bridging social capital networks. It intends to serve as a bridge for students and scholars within the various social sciences. It explores the different scientific approaches that are needed if international research is to embrace both the bright and the more shadowy aspects of social capital.
The troika of sociology, political science and economics / Gert Tinggaard Svendsen, Gunnar Lind Haase Svendsen -- The meaning of social capital and its link to collective action / Elinor Ostrom, T.K. Ahn -- Cooperation : evidence from experiments / Anders Poulsen -- Grid-group analysis / D. Douglas Caulkins -- Social capital in the brain? / Michael Bang Petersen, Andreas Roepstorff, Søren Serritzlew -- Humour / Peter Gundelach -- Religio-philosophical roots / Ralph Weber -- Corruption / Eric M. Uslaner -- Social capital : the dark side / Peter Graeff -- Social capital in east-central Europe / Natalia Letki -- The state / Francisco Herreros -- The universal welfare state / Bo Rothstein -- The Nordic welfare state / Thora Margareta Bertilsson, Christian Hjorth-Andersen -- Tax compliance / Lars P. Feld -- The environment / Kim Mannemar Sønderskov -- The labour market / Fabio Sabatini -- Locational choice, ethnicity and assimilation / Gil S. Epstein -- Making integration work / Peter Nannestad -- Economic inequality / Henrik Jordahl -- Economic growth / Christian Bjørnskov -- The macro perspective on generalized trust / Martin Paldam -- Mixed methods assessment / Veronica Nyhan Jones, Michael Woolcock -- The sociability of nations : international comparisons in bonding, bridging and linking social capital / Roger Patulny -- Building social capital / Robert Chase, Rikke Nørding Christensen.
Keywords: Social capital (Sociology); Sociology; Political science; Economics